The role of the new information technologies in emergency mitigation, planning, response and recovery - Fischer, Henry W. III (1998)
Multimedia, CD-ROM, DVD, Internet, Web Sites and e-mail are all part of a constantly changing, emerging array of the new information technologies which are being utilized in public education and are increasingly being applied to emergency planning and training activities to enhance emergency preparedness. Illustrations are presented which demonstrate the utility of multimedia, CD-ROM, and Internet applications to this process. These technologies will be applied to demonstrate how emergency planners may more effectively accomplish their mission to educate the larger community on a variety of issues such as the need to adopt proposed mitigation strategies, to respond to disaster warnings and evacuation suggestions. These technologies will also be applied to demonstrate how response and recovery information can be readily disseminated to an impacted area. Applications will also be provided which demonstrate the utility of these technologies in enhancing training activities for emergency personnel as well as extending the opportunity for such training beyond the time and place of the original trainer. - Reproduced
Keywords: Technology; Emergency services; Distance learning; Disaster recovery; Disaster planning; Contingency planning